How do customer anxiety levels impact relationship marketing in electronic commerce? - Bui Thanh Khoa; Tran Trong Huynh (Cogent Business & Management, 2022)
E-commerce is no longer a transaction in developed countries but has been popular worldwide. However, building long-term customer relationships is challenging for online businesses because of consumers' anxiety levels in the transaction process. This study aimed to expose the moderating effect of anxiety on relational marketing between the business and customers in the online market. The mixed method was applied to achieve the research objective. Qualitative research was mainly used to confirm and develop research items. Moreover, quantitative research was to test the research hypotheses through a survey of 917 respondents who experienced shopping online and faced severe problems in the past. The positive relationship between perceived mental benefits, online trust, hedonic value, and electronic loyalty was confirmed via Partial Least Squares Structural Equation Modeling. The anxiety levels impact the relationship between perceived mental benefits and electronic loyalty, online trust, and electronic loyalty. The mediating role of online trust and hedonic value is confirmed. Finally, the study proposed the managerial implication of maintaining customer relationships by increasing the mental benefits, customer trust, and hedonic value and reducing anxiety.
Keywords: 650; hedonic value; anxiety levels; electronic loyalty; online trust; perceived mental benefits